Otimização dos campos de proteção nas técnicas de desacoplamento dinâmico contínuo - Zanni Junior, Paulo Eduardo (2023)
In this research project, we investigate the method known as continuous dynamical decoupling, which is based on the use of continuously applied external fields to maximize the fidelity of quantum logical operations performed on a qubit experiencing decoherence. In our model, we assume an open quantum system in which a qubit continuously interacts with its surroundings, and thus we say that the qubit is coupled to the environment, which irreversibly disturbs it, causing decoherence. The continuous dynamical decoupling tells us that assuming a known error operator and an environment represented by a field of scalar bosons at a finite temperature, decoherence during logical operations can be efficiently reduced by applying a superposition of two external vector fields: one rotating orthogonally to the direction of the other, which remains static. The main objective of this project is to improve the method by finding optimized directions of external fields that, when continuously applied, maximize the fidelity of logical operations performed on a qubit. To achieve this, we will need to numerically solve the master equation of the system – where the external fields will be applied with variable directions (variable angles) during the optimization process – in order to find the best protective fields for a given logical operation. Finally, we present the results obtained for a qubit in an environment with ohmic spectral density and briefly discuss the findings.